Interspecific Killing of an Arctic Fox by a Red Fox at Prudhoe Bay, Alaska - Pamperin, Nathan J.; Follmann, Erich H.; Petersen, Bill (ARCTIC, 2009)
We report on the interspecific killing of an arctic fox (Alopex lagopus) by a red fox (Vulpes vulpes) in the Prudhoe Bay Oilfield, Alaska, an event that was captured on video in November 2004. Both the video and evidence from observation indicate that this may be a case of intraguild predation. The interaction represents an extreme example of competitive behavior and suggests that increased contact between these two sympatric canids in northern Alaska could be detrimental to arctic foxes. Dans un champ pétrolifère de la baie Prudhoe, en Alaska, un renard roux (Vulpes vulpes) a tué un renard arctique (Alopex lagopus). Il s’agit là d’une attaque interspécifique qui a été captée sur vidéo en novembre 2004. La vidéo et les indices prélevés au moment de l’observation laissent croire qu’il pourrait s’agir d’une prédation intraguilde. Cette interaction représente un exemple extrême de comportement compétitif et laisse supposer que le contact accru entre ces deux canidés sympatriques du nord de l’Alaska pourrait nuire aux renards arctiques.